Dissociative Experiences Scale: Psychometric Analysis in Puerto Rico and Contributions to the Discussion of the Factor Structure - González-Rivera, Juan (2023)
Introduction: The Dissociative Experiences Scale (DES-II) is a widely used psychometric tool to assess dissociative symptoms. Over the years, it has been the subject of numerous studies and research in various fields of psychology and psychiatry. Numerous studies have supported the validity and reliability of the DES-II as a reliable measure of dissociative experiences. The most problematic aspect of the DES-II is the inconsistency in its factor structure. Objective: This research aimed to examine the psychometric properties of the DES-II in a clinical and non-clinical sample from Puerto Rico. Method: This research had an instrumental design. An availability sampling of 341 adult participants was used. Several competing models of the DES-II were analyzed, including a bifactor model. Result: Psychometric analyses concluded that the scale has a unidimensional structure, strong reliability, and construct validity. All 28 items met adequate discrimination values. Participants with dissociative disorders obtained higher means on the DES-II than the other diagnostic groups. Furthermore, the more adverse experiences in childhood, the more dissociative experiences in adulthood. Conclusion: The DES-II should be treated and interpreted as a unidimensional dissociation index rather than a multidimensional instrument. This study will advance further research on dissociation and dissociative disorders in Puerto Rico and Latin America.